Respuesta :

Answer:

The value of x will be:

  • [tex]x=-5[/tex]

Step-by-step explanation:

Given the equation

[tex]4-2(x+7)=3(x+5)[/tex]

Multiply (or distribute) each term in parenthesis on L.H.S by -2, and multiply (or distribute) each term in parenthesis on R.H.S by 3.

[tex]4-2x-14=3x+15[/tex]

simplifying the equation by subtracting 14 from the L.H.S

[tex]-10-2x=3x+15[/tex]

Subtracting 15 from both sides

[tex]-10-2x-15=3x+15-15[/tex]

[tex]-25-2x=3x[/tex]

combining the like terms

[tex]-25=3x+2x[/tex]

[tex]-25=5x[/tex]

dividing both sides of the equation by 5

[tex]\frac{-25}{5}\:=\:\frac{5x}{5}[/tex]

[tex]-5=x[/tex]

Therefore, the value of x will be:

  • [tex]x=-5[/tex]
ACCESS MORE